Efeitos do butóxido de piperonila na toxicidade do organofosforado Temefós e o envolvimento de esterases na resistência de Aedes aegypti (Díptera: culicidae) ao Temefós - Pereira, Boscolli Barbosa (2008)
Resistance to insecticides remains a major problem for the successful control of Aedes aegypti, which is currently one of the most widespread disease vectors in the world. The organophosphorous insecticide temephos (TE) has been used to control pyretroid-resistant populations of A. aegypti. Piperonyl butoxide (PBO) has been used as a synergist of insecticides to control insects. PBO is known to inhibit the bio-activation of organophosphorous insecticides. This study was conducted to evaluate the effect of PBO on TE toxicity to A. aegypti using some bioassay techniques. These bioassays in both the susceptible and TE-resistant L4 larvae of A. aegypti strains revealed that at 0.25, 0.5, 1 and 2% conentration, PBO significantly (p< 0.05; Chi-square test for heterogeneity) synergized TE toxicity. We demonstrated that enhanced esterase activity was associated with survivability of L4 larvae of A. aegypti exposed to TE alone. Results of biochemical assays suggest that PBO had significant (p< 0.05; Tukey, Kramer) effect on the esterase activity in the A. aegypti. The observed synergistic effect of PBO at mentioned concentrations on TE toxicity to A. aegypti could be explained by reduced esterase activity due to PBO inhibition.